ANALISIS KESTABILAN MODEL MATEMATIKA KECANDUAN ALKOHOL TIPE SDAR - Giovani Sanit; Leonardus Obe; Nugraha Dethan; Faustianus Luan (Program Studi Matematika, Universitas Timor, 2025)
Alcohol is a psychoactive substance that is addictive. Psychoactive substances are a class of substances that act selectively, especially on the brain, which can cause changes in a person's behavior, emotions, cognition, perception and consciousness. Alcohol is an addictive substance that can cause addiction and dependence. Alcohol addiction is a condition when a person experiences an addiction to alcohol and is difficult to control until he becomes dependent. Alcohol addiction occurs due to consuming too much alcohol so that the level is sufficient to cause mental changes and experience a sensation of satisfaction when consumed. The habit of consuming alcohol for teenagers begins due to a lack of knowledge and invitations, persuasion and seduction from friends which make a teenager want to try consuming alcohol. After getting to know and feel the sensation of consuming alcohol, a teenager gradually begins to fall into the world of alcohol and begins to increase his consumption due to the free social environment among teenagers. This research aims to build a mathematical model of SDAR type alcohol addiction. Based on the research results, two equilibrium points were obtained, namely the equilibrium point free from alcohol addiction and will be stable when and the equilibrium point where there is alcohol addiction and will be stable when . The simulation results were observed in two conditions, namely when and the value was obtained, meaning that the rate of movement from the population of teenagers who tried to consume alcohol to alcohol addiction was still small, so that teenagers who Alcohol addiction will decrease until alcoholics will disappear from the population over time. Then when and the value is obtained, meaning that the rate of movement from the population of teenagers who try to consume alcohol to alcohol addiction is increasing until there will be more and more alcoholics and will increase in the population as along the time.